Drought tolerance of two field-grown clones of Coffea canephora - DaMatta, Fábio M.; Chaves, Agnaldo R. M.; Pinheiro, Hugo A.; Ducatti, Carlos; Loureiro, Marcelo E. (Elsevier, 2003)
We compared tolerance to soil drought of two field-grown clones of Coffea canephora (clone 46, drought-sensitive; and clone 120, drought-tolerant). Under irrigation, there were no marked differences between the clones in water relation parameters, gas exchange and total leaf area. Under rainfed conditions, clone 46 showed osmotic adjustment and increased tissue rigidity. These adjustments, however, were incapable of preventing substantial decreases in xylem pressure potential. By contrast, clone 120 did not exhibit osmotic adjustment, but was able to increase tissue elasticity and to maintain xylem pressure potentials to a greater extent than clone 46 (despite having twice the total leaf area of this clone). Stomatal conductance was lowered by drought in clone 120 but not in clone 46. Carbon assimilation per unit leaf area in both clones remained unaffected under stress. Long-term water use efficiency (WUE), as estimated through carbon isotope discrimination, was consistently greater in clone 120 than in clone 46. Because of these traits, clone 120 was better able to postpone dehydration and to maintain whole-tree photosynthesis. It is proposed that these features should decisively contribute to buffer its productivity in drought-prone areas. © 2002 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: Carbon isotope discrimination; Coffea canephora; Coffee; Drought stress; Gas exchange; Water relations; Cloning; Dehydration; Drought; Irrigation; Isotopes; Photosynthesis; Tissue; Plants (botany)